Bernstein trace - Haghverdi, Esfandiar (Springerplus, 2016)
We introduce the notion of relative trace which is motivated by an observation about the category of vector spaces and linear transformations and builds upon the categorical trace of Joyal, Street, and Verity. Furthermore, we define a new categorical trace based on a trace formula first introduced by J. Bernstein.